Extracellular biosynthesis of iron-based nanoparticles from isolated bacteria from iron waste soil / Mohammad Zabarjad Jeffidin - Jeffidin, Mohammad Zabarjad (2016)
Microorganisms such as bacteria encompass a various range of enzymatic activity and capable of catalyzing a variety of biochemical reactions as well as evolve according to the environment they lived. Some of those bacteria are capable of converting the metal element to smaller particle known as nanoparticles. Nanoparticles have various used in daily life and needed to be produced in a way that can save the cost. The cost to produced nanoparticles can be cut down if it is produced in natural way by using bacteria. The aims of this study were to isolate, screen and identify the bacteria that can synthesize iron nanoparticles. The bacteria samples were obtained from iron waste soil in UiTM Jengka. The bacteria in each soil sample were grown in Luria agar and differentiated according to the shape of the colonies. Each isolates were grown in Luria broth and centrifuged to get the supernatant. The supernatants were mixed with Iron (III) Oxide, Fe2O3 and screen for its ability to produce iron nanoparticles with Ultraviolet-Visible Spectrophotometry (UV-Vis) in the range 470 nm of wavelength and the colour changes of the solution from brick red to dark brown was observed. The result of this study shows out of 6 samples, bacteria E show remarkable result that utilized 40% of iron (III) oxide to form iron nanoparticles. Bacteria E is a Gram positive rod-shaped bacterium that are motile, catalase positive and give negative result to Acid-fast stain, Indole test and methyl red test. As the conclusion, Bacteria E is suggested to be from Bacillus group and potentially can be used in iron nanoparticles industries.